Evaluasi Program Pendidikan Antikorupsi dalam Pembelajaran - Hambali, Ginanjar (Komisi Pemberantasan Korupsi, 2020)
This study aims to evaluate the anti-corruption education program that is encouraged by the Corruption Eradication Commission, through the Context, Input, Process, Product (CIPP) model. This evaluation is limited since of signing the memorandum of understanding (MoU) with four ministries on anti-corruption education entered the curriculum in 2018. This research is a formative evaluation study and is descriptive qualitative in nature. In terms of context, the background of the problem is sufficient reason for anti-corruption education to be included in the curriculum, while the selection of strategies and learning methods is an inseparable part. From the input side, the implementation of anti-corruption education is not enough for training, but must be accompanied by assistance. Learning materials and materials must be distributed even more. From the aspect of the process, the practice of anti-corruption learning is not very visible. Finally, in terms of products, anti-corruption education programs have not been carried out in many regions. The difference between regions that have carried out anti-corruption education and those who have not yet implemented it is not significant. This research recommends to increase the number of regions that implement anti-corruption education programs, improve training and mentoring anti-corruption education practices, publish anti-corruption learning innovations based on teacher practices.